New aspects of muon–electron nuclear conversion; Physics Letters B; Vol. 544, iss. 1-2 - Simkovic F.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Gutsche Th.; Faessler A.; Kovalenko S. (2002, 2002)
Title screen